Citra Dialog Antara Agama Dalam Persfektif Islam dan Kristian : Analisis Awal - Fikra Najtama (TASAMUH: Jurnal Studi Islam, 2015)
This paper aims to expound religious dialogue from thehistorical perspective in looking into its scenario. In apprehending aform of perspective on the concept of interfaith dialogue, the viewpoint ofIslam and Christian are referred to. An early stage of analysis is done inorder to comprehend to what extend does the new paradigm introducedby the Christian dialoguers influence the religious dialogue. This writingalso demonstrates religious dialogue in Malaysia from the perspectiveof Muslim and Christian scholars. Besides, this paper discovers thatthe interfaith dialogue scenario in Malaysia has its own distinguishedperspective as it is deeply embedded with revelation and is relevant inthe current plural society